Status Hukum Peraturan Otoritas Jasa Keuangan Terkait Perlindungan Hukum Terhadap Investor Pasar Modal Syariah - Diman Ade Mulada (STIS DAFA MATARAM, 2021)
This study aims to explain the legal status of the Financial Services Authority regulations governing legal protection for Islamic capital market investors. The type of research used is normative legal research with the Legislation approach and the Conceptual approach. The results of this study are that based on the provisions of Article 4 of Law Number 8 of 1995 concerning the Capital Market, it is stated that the guidance, regulation and supervision of financial service activities in the capital market sector is carried out by Bapepam LK which then transfers the authority to the OJK after the enactment of the Act. Law No. 21 of 2011, so that based on the Act, Article 8 gives authority to OJK to stipulate OJK regulations as a form of regulatory task. Thus, several Financial Services Authority regulations that regulate legal protection for Sharia Capital Market investors have a valid legal status, because they are in accordance with Law No. 12 of 2011 in Article 8 Paragraph (1) which regulates the types of Legislation and Regulations. Invitations other than those referred to in Article 7 Paragraph (1) are recognized to exist and have binding legal force as long as they are ordered by a higher Legislation or formed based on authority